(untitled) (Research, Society and Development, 2020)
The need for investment in improving quality, productivity, and low cost and process energy savings is a growing concern of the ceramist sector. The drying process consists in moisture removal from a material through heating, involving high energy consumption. In this sense, this work aim to study theoretically the drying of hollow ceramic solids with arbitrary shape using a phenomenological mathematical modeling based on the lumped capacitance method. Kinetic results of mass loss and heating of the hollow solid under different operating conditions are presented and analyzed. It was observed that the loss of moisture occurs at a slower rate than the heating rate of the material, and that the shape of the solid and its area / volume relationships strongly affect the heat and mass transport phenomena and that, depending on the intensity, can cause structural damages as cracks, deformations, warping and loss of the product.